Two Homes - Masurel, Claire; Denton, Kady MacDonald (Cambridge, MA, 2001)
A young boy named Alex enjoys the homes of both of his parents who live apart but love Alex very much.
Keywords: Divorce; Fiction; Parent and child; Fiction; Dwellings; Fiction